Active vitamin D regulates macrophage M1/M2 phenotypes via the STAT‐1‐TREM‐1 pathway in diabetic nephropathy. Issue 5 (27th November 2018) - Zhang, Xiaoliang; Zhao, Yu; Zhu, Xiaodong; Guo, Yinfeng; Yang, Ying; Jiang, Yuteng; Liu, Bicheng
Abstract: Aim: Imbalance of M1/M2 macrophages phenotype activation is a key point in diabetic nephropathy (DN). This study aimed to investigate whether active vitamin D (VD) suppresses macrophage transition to the M1 phenotype via inhibiting the high glucose‐induced STAT‐1 phosphorylation to reduce TREM‐1 expression. Methods: In vivo, pathological changes in kidney tissue were detected and the expression of CD68 TREM‐1, STAT‐1, M1 makers, and M2 makers were acquired in renal tissue of patients with DN and 18w DN rats. In vitro, RAW 264.7 cells were incubated in the presence of high glucose with or without VD. Silencing and overexpression of TREM‐1 and silencing and activate of STAT‐1 were explored to elucidate the underlying mechanism. The expression of TREM‐1 and STAT‐1 and the changes of macrophage phenotype were examined separately by western blot and immunofluorescence staining. Results: (a) Expression of TREM‐1, p‐STAT‐1, and M1 markers (iNOS and TNF‐α) were increased and positively correlated in kidneys from patients with DN. (b) In DN rats, the enlargement of glomerular surface area, expansion of glomerular mesangial matrix, the expression of CD68, TREM‐1, p‐STAT‐1, and M1 marker (iNOS) were significantly increased in comparison with the normal control group, whereas above changes were markedly decreased in the diabetic group treated with the VD group. (c) In vitro, VD significantly decreased high glucose‐induced CD68, TREM‐1, p‐STAT‐1, and M1 marker (iNOS) expression. However, above‐mentioned effects of VD are abolished when TREM‐1 is overexpressed or STAT‐1 is activated. Reductions in STAT‐1 expression decreased the TREM‐1 expression. Conclusion: VD can inhibit macrophage transition to the M1 phenotype through the STAT‐1/TREM‐1 pathway. Abstract : Vitamin D can inhibit macrophage transition to the M1 phenotype through the STAT‐1/TREM‐1 pathway.